Application of pressure injury preventive measures and bundles in home and community environments: a scoping review protocol - Ramos, Fabiana Tomé [UNESP]; Oliveira, Rhavenna Thais Silva [UNESP]; Avila, Marla Andreia Garcia [UNESP]; Andrade, Juliane [UNESP]; Moda Vitoriano Budri, Aglecia Vitoriano Moda [UNESP]; Alencar, Rúbia Aguiar [UNESP] (BMJ, 2025)
INTRODUCTION: Several studies have addressed the use of pressure injury preventive measures and bundles for hospitalised patients. However, there is a gap in research regarding the use of pressure injury preventive measures and bundles in the home environment. This scoping review aims to identify, explore and map the international literature on pressure injury preventive measures and bundles in the home and community environments. METHODS AND ANALYSIS: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews will be used to guide the reporting of this scoping review. The Joanna Briggs Institute guide will inform the methods. A modified version of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols will be used to guide the reporting of this scoping review protocol. An initial search was carried out in July 2024. The search will be conducted in electronic databases such as LILACS, SciELO, Scopus, PubMed, Embase, CINAHL, Cochrane Library and Web of Science. The search will be restricted to studies in English, Portuguese and Spanish, with no time restriction. Additional literature will be retrieved by reviewing the reference lists of the selected studies based on their titles. Two independent reviewers will carry out the data extraction process. Essential details, including the author, references and findings pertinent to the review questions, will be collected. The findings will be displayed through graphs, tables and figures, supplemented by a narrative summary. ETHICS AND DISSEMINATION: As this review will be conducted using secondary data, ethical approval is not required. Results will be shared with the international scientific community through conference presentations and publication in a high-impact journal. STUDY REGISTRATION: This scoping review was registered with the Open Science Framework registry (osf.io/m5gvn) on 8 August 2024.
Keywords: Nursing research; Preventive Health Services; Wounds and Injuries